Answer: Infinite solutions
Step by step explanation:
Combine the like terms in each side of the equation. Let’s start with the first half.
9x + -5x + -3 + -7
We can combine the terms with variables and the terms without
9x + -5x = 4x
-3 + -7 = -10
4x - 10 would be the first part of the equation. The second equation, do the exact same steps.
-3x + 7x = 4x
-1 + -9 = -10
4x - 10 is the second half of the equation.
4x - 10 = 4x - 10 is the entire equation. They are both exactly the same which means they are equal to each other. This means that no matter what number is put into the variable, x, they will be the same answer.